(untitled) - Prof. Dr. Michael Lingenfelder, Universität Marburg (für Betriebswirtschaftslehre); Prof. Dr. Norbert Berthold, Universität Würzburg (für Volkswirtschaftslehre) (WiSt - Wirtschaftswissenschaftliches Studium, 2023)
Up-to-date knowlegde of the main topics and proven methods in business and economics research is the key factor for success in both academia and business. Month by month, WiSt delivers this knowledge by presenting and discussing latest trends and current topics on the basis of models from the business and economics sciences. Language: German. For more information for authors and subscribers, see http://rsw.beck.de/cms/main?site=WiSt.